Upregulation of TLR2/4 Expression in Mononuclear Cells in Postoperative Systemic Inflammatory Response Syndrome after Liver Transplantation - Ziqing Hei; Xinjin Chi; Nan Cheng; Gangjian Luo; Shangrong Li (Mediators of Inflammation)
Background. To explore the relationship between Toll-like rpheral blood mononuclear cells (PBMC) and systemic inflammatory response syndrome (SIRS) in postoperative patients of liver transplantation (LT). Methods. Blood samples of 27 patients receiving LT were collected at T1 (after induction of anaesthesia), T2 (25 minutes after the beginning of anhepatic phase), T3 (3 hours after graft reperfusion), and T4 (24 hours after graft reperfusion). The expression of TLR2/4 on PBMC and serum concentration of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-8 were measured. The patients were divided into SIRS group (n=12) and non-SIRS group (n=15) for analysis. Results. Blood loss and transfusion were higher in the SIRS group than in the non-SIRS group. Both the preanhepatic and anhepatic phase were significantly longer in the SIRS group. The TLR2/4 expression on PBMC as well as serum TNF-α, IL-1β, and IL-8 were significantly higher at T3 and T4 than that at T1 and T2 in the SIRS patients. The expression of TLR4 on PBMC is positively correlated to serum TNF-α, IL-8. Expression of TLR2/4 on PBMC and serum concentrations of TNF-α, IL-1β, did not differ among the 4-time points in non-SIRS patients. Conclusions. Upregulation of TLR2/4 expression on PBMC may contribute to the development of postoperative SIRS during perioperative period of LT.